Novice Occupational Therapy Practitioners' Use of Occupation in Practice: A Scoping Review. Issue 2 (3rd April 2023) - Jones, Kristin Bray; Schell, Barbara A. Boyt; Neville, Marsha; Pickens, Noralyn Davel
Abstract: An occupation-centered perspective is a foundational component defining occupational therapy practice. A scoping review was conducted of research studies from 2002 − 2020 describing novice occupational therapy practitioners and occupation. Ten articles met the inclusion criteria. Novices acknowledged that using occupation was a source of professional tension, describing a mismatch between their education and workplace expectations. The cognitive load of occupation-centered practice influenced novices' avoidance of occupation. Few articles address novices' experiences using occupation in their practice. Existing research primarily addresses barriers limiting novices' use of occupation such as lack of supervision and confidence.